(3fbO GdGbJQGMGJ GdeUQjIs - (3Bd cGTa GdZWGA, eMeO QVG Hf gGOj Hf YHGS, J (B1366 (3g`s
(3ChdgG (B:s
(3hgPG cJGH jTJed Ydi GdaUd GdChd efg Ydi faS GdGbJQGMGJ , GdaUd GdKGfj fbOgG ef GdYdGeI GdeQMhf GdTjN eMeO QVG GdTjN gGOj cGTa GdZWGA (B...s
(3BNQgG (B:s
.. (3Ef CQGOhG HgG ZjQgG abO YQaJ eG dCHhGH GdHdGZI ef GdCgejI hGdaGFOI GdJj JSJOYj hLhH OQGSJgG hGdGWdGY YdjgG hgfGc CeQ CNQ dG jSY GdeLGd GdJYQV dgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\127s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdCOHs